Who Maps Middle Eastern Geographies in the Digital Age? Inequalities in Web 2.0 Cartographies in Israel/Palestine - Glasze, Georg; Bittner, Christian (Media and Mapping Practices in the Middle East and North Africa, 2021)
Cartographic practices have long been the domain of professionalized and centralized actors from governmental or commercial spheres. Inspired by the emergence of mapping practices in the age of Web 2.0, however, new forms of mapping may offer a bottom-up alternative. Indeed, the mapping platforms Wikimapia and especially OpenStreetMap have proven that geographical information and maps can be generated via crowdsourcing by cartographic amateurs. Yet, several studies have excavated powerful exclusion mechanisms in such Web 2.0 cartographies, showing that user-generated geographical content is often produced by privileged demographic groups. This chapter will explore these patterns of exclusion and inclusion in OpenStreetMap and Wikimapia in the examples of the Gaza Strip and Jerusalem. <br
Keywords: Cartography; Israel; OpenStreetMap; Palestine; volunteered geographical information; Wikimapia